Data decoding based on iterative spectral image reconstruction for display field communications - Pankaj Singh (ICT Express, 2021)
This letter proposes a powerful method to reconstruct the spectral image frames for increasing data transmission capability in Display Field Communication (DFC) systems. The proposed method reconstructs the spectral image iteratively using the good data symbol estimates fed back by the camera decoder. To begin with, initial image is estimated by means of known pilot symbols. Then, hard symbol decisions obtained by iterative decoding are used to improve the quality of the reconstructed image. The proposed technique selects good data pixels using hard information from the decoder and performs re-estimation of the image pixels. From numerical simulations, we show that the proposed method significantly boosts the data transmission capacity of the DFC system over the conventional DFC that uses reference frames.